2009
DOI: 10.1107/s1600536809026701
|View full text |Cite
|
Sign up to set email alerts
|

Cynaratriol, a sesquiterpene lactone fromCentaurea musimomum

Abstract: The title compound [systematic name: 3,8-dihydr­oxy-3-(hydroxy­meth­yl)-9-methyl-6-methyl­enedeca­hydro­azuleno[4,5-b]furan-2(3H)-one], C15H22O5, is a sesquiterpene lactone showing the typical tricyclic guaianolide skeleton which has been isolated, together with other related metabolites, from the plant Centaurea musimomum. The present study confirms the mol­ecular structure, assigned by 1H NMR and MS spectroscopy, as well as the the 11β-hydroxy­methyl, 3β-hydr­oxy and 4α-methyl stereochemistry. The crystal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…papposa , C. granata , C. pullata and C. maroccana [ 43 ]. In addition, guaianolides and elemanolides have been isolated from Centaurea, including four guaianolides and cynaratriol from C. musimomum [ 44 ]; centaurpensin and 13-acetyl solstitian A from C. solstitialis [ 45 ]; cebellin M from C. bella [ 46 ]; the elemanolideshierapolitanins A, B, C, and D isolated from C. hierapolitana [ 22 ]; and 13- N -proline melitensin and 13- N -proline-6α, 8α, 15-trihydroxy elema-1,3-diene-oic acid from C. polyclada [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…papposa , C. granata , C. pullata and C. maroccana [ 43 ]. In addition, guaianolides and elemanolides have been isolated from Centaurea, including four guaianolides and cynaratriol from C. musimomum [ 44 ]; centaurpensin and 13-acetyl solstitian A from C. solstitialis [ 45 ]; cebellin M from C. bella [ 46 ]; the elemanolideshierapolitanins A, B, C, and D isolated from C. hierapolitana [ 22 ]; and 13- N -proline melitensin and 13- N -proline-6α, 8α, 15-trihydroxy elema-1,3-diene-oic acid from C. polyclada [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various Centaurea species have certain biological activities, such as antifungal, 4 antimicrobial, 5 anti-ulcerogenic, 6 anti-inflammatory, 7 antioxidant, 8 antiviral, 9 anti-Helicobacter pylori, 10 anticancer and cytotoxic. 11 The genus was also the subject of interest of several phytochemical investigations for their potentially active constituents, particularly sesquiterpene lactones [12][13][14][15][16] and flavonoids. 17,18 As a part of ongoing and systematic investigations on the composition of the plants of this genus, [19][20][21][22][23][24] the chemical constituents of the extracts of the aerial parts of three species: C. tomorosii Micevski, C. soskae Hayek and C. galicicae Micevski, all are endemic to Balkan Peninsula, were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been stated that Centaurea species exerts a vide range of biological effects including anti-microbial, anti-fungal, antiplasmodial (Karamenderes et al 2006;Kaskoos 2013), anti-ulcerogenic, anti-oxidant, anti-viral, antiprotozoal and anti-cancer properties (Ugur et al 2009a(Ugur et al , b, 2010Erol-Dayi et al 2011;Kilic 2013;Pires Tania et al 2018). Moreover, Centaurea was also a source of some phytochemical studies for its potentially active substance especially flavonoids (Flamini et al 2004;Mishio et al 2006) and sesquiterpene lactones (Gonzalez et al 1984;Medjroubi et al 2005;López-Rodriguez et al 2009). In another study, Escher et al (2018) identified chlorogenic, caffeic, ferulic, and p-coumaric acids, isoquercitrin, and coumarin as major compounds of Centaurea genus also.…”
Section: Introductionmentioning
confidence: 99%